Ethnic stereotypes in the english pamphlet literature - Farkas, Attila (Studia Mundi – Economica, 2015)
The study initiates the alternative mode of researching stereotype. To this effect first it reviews those results of examining the theme that have been reached by the modern social science, then itturns to the other methodology that is possible and promising results, that is a special synthesis of the philosophy of the classical rhetoric and intellectual history. It applies this methodology for two outstanding writing of the English pamphlet literature, and it helps to outline the moral position of the stereotype.